Optimizing government communication on environmental issues: Visual strategies for public engagement - Iwan, Iwan; Wibowo, Kunto Adi; Rahmawan, Detta (Universitas Padjadjaran, 2024)
Background: Visual elements in content play a crucial role in influencing user engagement on social media platforms. This study focuses on Instagram, a widely used social media platforms in Indonesia, using the official account of a government institution, that is the Instagram account of the Ministry of Environment and Forestry (MoEF) of the Republic of Indonesia for analysis. It is important to increase public awareness about environmental challenges, such as land degradation and the decline of animal populations, and to disseminate information about preserving Indonesia’s native fauna and flora through conservation programs. Purpose: This study aims to analyze and compare the visual factors in each Instagram post of the MoEF, to evaluate user interaction with the account. Instagram was chosen because the institution is more active on this media platform compared to others. Methods: This study employed a quantitative content analysis, using one-way ANOVA analysis to review potential variations in user interaction across different visual factors. Results: The results revealed variation among categories in terms of content type (F = 8.146; p = 0.001), visual aesthetics (F = 8.299; p = 0.004), and presentation modality (F = 4.341; p = 0.038). This finding suggests that government Instagram accounts need to carefully consider visual factors to enhance user interaction. Implications: This study provides guidance for government institutions on enhancing environmental awareness through effective visual communication strategies on social media, particularly Instagram.